(untitled) (Revista Innova Educación, 2021)
In this article we sought to summarize the entire process that children with special educational needs have gone through, starting with the historical journey to be recognized as subjects of rights, the process that has been carried out to integrate them into the classroom in class having consider the policies regarding the issue and finally, the difficulties that continue to arise with children with disabilities within the Colombian educational system. The review was carried out by means of the snowball method, in which one author referred us to another who could continue to contribute to the subject. The results show the characterization of the needs of the vulnerable population with differential disability in terms of respecting the fundamental and universal rights of education to the target population in question, strengthening concepts on issues of functional diversity, based on the implementation of a solid strategy and supported by universal education for the necessary accessibility for the population with varied disabilities.